Mini Research: Analyzing the Relationship between Listening to Murottal Al Qur’an Surah Al Baqarah Verses 1-10 to Beta Waves with Learning Concentration - Heni Sumarti; Muhammad Syafiul Huda; Fahira Septiani; Affa Ardhi Saputri; Arifah Riana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2023)
Concentration in learning has a big impact on determining learning outcomes. Some of the conditions experienced by students who find it difficult to maintain concentration during the learning process are caused by many factors. Among them is the atmosphere of a noisy learning environment. One way to determine the learning concentration condition is by measuring beta brain waves using Electroencephalography (EEG). This study aims to analyze the effect of the murottal stimulus of Al Baqarah verses 1-10 on beta brain wave activity and its relationship with learning concentration. The research method used is experimental. Subjects in this study were 6 students of UIN Walisongo Semarang, with inclusion criteria ranging from 20-23 years old, Muslim, not hearing impaired, physically and mentally healthy, and not using drugs. The stages of research consisted of 4 stages; first, the research subjects carried out the pre-test without stimulus; second subject measured their brain waves without stimulus; third, subjects measured brain waves with stimulus; and finally, the research subjects carried out the pre-test with stimulus. The analysis results using the T-test, which stated that the average comparison of beta brain waves in the two groups before and after being given the murottal Al-Qur’an stimulus showed a p-value of 0.0003 (p<0.05). While the results of the pre-test and post-test T-test showed a p-value of 0.017 (p<0.05). It shows that the murottal stimulus of Al Baqarah verses 1-10 effects changes in beta waves and the level of learning concentration.